Pengaruh e-WOM Terhadap Niat Pembelian Kain Tenun NTT - Nadia Saryta Panta; Gustaf Wijaya; Santi Isnaini; Dina Septiani (Peneliti.net, 2023)
Ethnic Weaving is one of the traditional fabrics that has a very high cultural value. Indeed, woven cloth is not as popular as batik, but the beauty and cultural philosophy contained in woven cloth is not inferior to batik. Although not as popular as batik, Ethnic Weaving has its own uniqueness. The uniqueness of Ikat lies in the manufacturing process. To make beautiful woven cloth, woven craftsmen need months. This is because the tools used for weaving are still manual. Electronic word of mouth (eWOM) can be defined as positive or negative statements made by potential, actual, or former customers about a product or company that are made available to a wide range of people and institutions via the internet. The aim of this study was to identify the Influence of Electronic Word of Mouth on the purchase intention of NTT Ethnic Weaving. The research methodology used is in the form of content analysis, by looking at the effect of e-WOM on the purchase intention of NTT Ethnic Weaving. This research focuses on the purchase intention of NTT Ethnic Weaving. The results of the study show that e-WOM has a positive influence on purchasing intentions of NTT Ethnic Weaving.